English - have a go : student's book self study - Nery, Caryn; Jenkin, Jim.; Noonan, Judi. (South Melbourne, Vic. : Oxford University Press, 1996)
The series, through the life of the Jones family, presents grammar, pronunciation and useful sentences for learners of English. There is also a segment introducing Australian families, including families from Korean, Italian, Chinese, English, Aboriginal and Greek backgrounds.
Keywords: English language; Foreign speakers; English language; English language -- Problems, exercises, etc; English language -- Study and teaching -- Textbooks for foreign speakers